Relationship between myocardial bridge compression severity and haemodynamic perturbations. Issue 7 (19th May 2019) - Javadzadegan, Ashkan; Moshfegh, Abouzar; Hassanzadeh Afrouzi, Hamid
Abstract: Objectives: This study aims to examine the alteration in coronary haemodynamics with increasing the severity of vessel compression caused by myocardial bridging (MB). Methods: Angiography and intravascular ultrasound were performed in 10 patients with MB with varying severities of systolic compression in the left anterior descending (LAD) artery. Computer models of MB were developed and transient computational fluid dynamics simulations were performed to derive distribution of blood residence time and shear stress. Results: With increasing the severity of bridge compression, a decreasing trend was observed in the shear stress over proximal segment whereas an increasing trend was found in the shear stress over bridge segment. When patients were divided into 2 groups based on the average systolic vessel compression in the whole cohort (%CRave = 27.38), patients with bridges with major systolic compression (>%CRave ) had smaller shear stress and higher residence time in the proximal segment compared to those with bridges with minor systolic compression (<%CRave ) (0.37 ± 0.23 vs 0.69 ± 0.29 Pa and 0.0037 ± 0.0069 vs 0.022 ± 0.0094 s). In contrast, patients with bridges with major systolic compression had greater shear stress in the bridge segment compared to those with bridges with minor systolic compression (2.49 ± 2.06 vs 1.13 ± 0.89 Pa). No significant difference was found in the distal shear stress of patients with bridges with major and minor systolic compression. Conclusion: Our findings revealed a direct relationship between the severity of systolic compression of MB and haemodynamic perturbations in the proximal segment such that the increased systolic vessel compression was associated with decreased shear stress and increased blood residence time.